2022
DOI: 10.1039/d2ma00646d
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the nonlinear susceptibility and linear parameters upon annealing Ag60−xSe40Texnanostructured films for nonlinear and photonic applications

Abstract: The current report is focused on the annealing-induced changes in structural, non-linear/linear optical, and surface morphological changes of the nanostructured Ag60-xSe40Tex (x=0,5,10,15 %) films. The increase in crystallinity with annealing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…36 αhν = B ( hν − E g ) m here the constant ‘ B ’ is dependent on the transition probability, ‘ m ’ is an index that have different values depending on the type of electronic transition that causes absorption. 37 Here the direct optical bandgap is evaluated, as the Ag 10 In 15 S 15 Se 60 thin films showed the crystalline nature. The graph of ( αhν ) 2 versus hν is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…36 αhν = B ( hν − E g ) m here the constant ‘ B ’ is dependent on the transition probability, ‘ m ’ is an index that have different values depending on the type of electronic transition that causes absorption. 37 Here the direct optical bandgap is evaluated, as the Ag 10 In 15 S 15 Se 60 thin films showed the crystalline nature. The graph of ( αhν ) 2 versus hν is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…the reciprocal of α . 50 The change in ‘ δ ’ as a function of energy is presented in Fig. 8(a), which shows the reduction of δ with hν .…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the absorption onset for the optical spectra is red-shifted toward higher wavelengths, thus indicating the decrease in the bandgap energy value (Figure a). The absorption ability is characterized by the absorption coefficient (α), which is obtained from the primary transmission ( T ) and using the thickness of film ( d ) from the formula: α = 1 d log true( 1 T true) …”
Section: Resultsmentioning
confidence: 99%